Ultrasound field characterization and bioeffects in multiwell culture plates - Patel, Upen S (J Ther Ultrasound, 2015)
BACKGROUND: Ultrasound with frequencies in the kilohertz range has been demonstrated to promote biological effects and has been suggested as a non-invasive tool for tissue healing and repair. However, many challenges exist to characterize and develop kilohertz ultrasound for therapy. In particular there is a limited evidence-based guidance and standard procedure in the literature concerning the methodology of exposing biological cells to ultrasound in vitro. METHODS: This study characterized a 45-kHz low-frequency ultrasound at three different preset intensity levels (10, 25, and 75 mW/cm(2)) and compared this with the thermal and biological effects seen in a 6-well culture setup using murine odontoblast-like cells (MDPC-23). Ultrasound was produced from a commercially available ultrasound-therapy system, and measurements were recorded using a needle hydrophone in a water tank. The transducer was displaced horizontally and vertically from the hydrophone to plot the lateral spread of ultrasound energy. Calculations were performed using Fourier transform and average intensity plotted against distance from the transducer. During ultrasound treatment, cell cultures were directly exposed to ultrasound by submerging the ultrasound transducer into the culture media. Four groups of cell culture samples were treated with ultrasound. Three with ultrasound at an intensity level of 10, 25, and 75 mW/cm(2), respectively, and the final group underwent a sham treatment with no ultrasound. Cell proliferation and viability were analyzed from each group 8 days after three ultrasound treatments, each separated by 48 h. RESULTS: The ultrasonic output demonstrated considerable lateral spread of the ultrasound field from the exposed well toward the adjacent culture wells in the multiwell culture plate; this correlated well with the dose-dependent increase in the number of cultured cells where significant biological effects were also seen in adjacent untreated wells. Significant thermal variations were not detected in adjacent untreated wells. CONCLUSIONS: This study highlights the pitfalls of using multiwell plates when investigating the biological effect of kilohertz low-frequency ultrasound on adherent cell cultures.